Analisis harga dan kualitas produk dalam meningkatkan keputusan pembelian (studi kasus Mie Ayam Donoloyo Cabang Pondok Rajeg Cibinong) - Revandy, Ferdy Damas; Handayani, Eva Mayfa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
The growing competition in the culinary business requires entrepreneurs to understand the key factors that influence consumer purchasing decisions. This study aims to analyze how price and product quality contribute to enhancing purchasing decisions at Mie Ayam Donoloyo, Pondok Rajeg Cibinong branch. This research employs a descriptive qualitative approach, using in-depth interviews and direct observation as data collection techniques. The findings reveal that consumers carefully consider affordable pricing, consistent taste, hygiene of presentation, and the overall consumption experience before deciding to purchase. Competitive pricing combined with a unique flavor profile serves as a key driver for repeat purchases and consumer loyalty. This study offers valuable insights for MSME culinary businesses in developing marketing strategies centered on customer value.